Modeling diet in times of change: The case of Quitor, San Pedro de Atacama, Chile. (June 2016) - Pestle, William J.; Torres-Rouff, Christina; Hubbe, Mark
Abstract: The transition from the Middle to Late Intermediate Period in the south-central Andes saw major changes in the lifeways of peoples across northern Chile; as far-flung networks of exchange and interaction broke down, social stressors and social conflict increased. In the present work, we present isotopic data from a sample ( n  = 58) of humans drawn from several cemeteries of the Quitor ayllu, in the San Pedro de Atacama oases, and we use Bayesian mixture modeling to explore the effects of these broad social, economic, and political changes on synchronic and diachronic patterns of dietary variation. A series of hypotheses dealing with both temporal changes in diet and differences between the typical diets of females and males are tested. Ultimately, our research suggests that the disarticulation of the large interregional exchange networks of the south-central Andes at the end of the Middle Period significantly impacted the diets and lifestyle of local populations. This work also shows how the use of linear mixture modeling facilitates a more nuanced interpretation of dietary composition than visual inspection or regression analysis of isotopic data. Highlights: Isotopic analysis of Middle and Late Intermediate Period individuals was attempted. Bayesian modeling supports hypothesis of Middle Period dietary variability. Models found less variance in diets of Late Intermediate Period. Sex-based differences in diet were greater for Middle Period.